Hydraulic diffusivity of different concrete mixtures based on sorptivity and moisture concentration profiles - Juárez Ruiz, Lidia Argelia; Cano Barrita, Prisciliano Felipe de Jesús; Castro Borges, Pedro (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
Unsaturated flow in porous media theory relates hydraulic diffusivity with water content assuming an exponential or power dependence on water saturation. Water sorptivity, a porous material property, describes the capillary absorption rate of a porous material exposed to a water source. It is an important parameter describing the concrete cover quality of reinforced concrete. Some authors suggest that knowing the sorptivity enables one to obtain the hydraulic diffusivity. This work is based on a previous research carried out to determine the effect of curing conditions on the drying and capillary water absorption of four concrete mixtures. The objective of this paper is to determine the hydraulic diffusivity of different concrete mixtures from water content profiles obtained with Magnetic Resonance Imaging (MRI) and from sorptivity, according to the method developed by Lockington and to demonstrate the validity of this solution for the concrete mixtures studied. Results showed that the exponential and power dependence of diffusivity with respect to the water content are not valid for all concrete types studied because rehydration effects may modify the capillary water ingress.